Endotracheal tube damage during surgically assisted rapid palatal expansion surgery; a case report - Badger, James (Journal of dental anesthesia and pain medicine: JDAPM, 2020)
Endotracheal tube damage is a well-known complication of maxillary surgery. We report a case of failure to ventilate due to superficial damage to the tubing between the cuff and pilot balloon in the nasal portion of a north facing Ring, Adair and Elwyn pre-formed endotracheal tube during Surgically Assisted Rapid Palatal Expansion surgery. The endotracheal tube was replaced uneventfully and surgery completed successfully. On reflection, we feel that that the vulnerable position of the cuff-pilot tubing significantly contributed to this critical incident and suggest that increased recognition of this is vital for the prevention of such cases in the future.